Partial melting of amphibolitic lower crust and subsequent melt-crystal separation for generation of the Early Eocene magmatism in eastern Himalaya - Dai, Zuowen; Yang, Zhiming; Li, Guangming; Xie, Yuling; Dong, Lei; Gao, Ke; Cao, Huawen (Frontiers in Earth Science, 2023)
The Himalayan leucogranites provide a good opportunity to investigate the crustal evolution of the southern Qinghai-Tibet Plateau. In this study, we present zircon U-Pb and monazite U-Th-Pb ages, zircon Hf isotopes and whole-rock Sr-Nd-Pb isotopes and major and trace elements for the Liemai two-mica granite, eastern Himalaya. Together with previously published data we revalued the petrogenesis of the Early Eocene magmatic rocks in this region and their geological implications. The zircon and monazite U-(Th)-Pb dating results showed that the Liemai two-mica granite was generated at ∼ 43 Ma, similar to adjacent Yardoi, Dala and Quedang adakitic two-mica granites, Ridang subvolcanic rocks and Yardoi leucogranite. The Liemai two-mica granite, similar to these coeval adakitic two-mica granites, is enriched in SiO2, Al2O3, Th, U, Pb, La, and Sr, and depleted in MgO, total iron, Yb and Y with high Sr/Y and (La/Yb)N ratios (showing adakitic affinities), and exhibits enriched Sr-Nd-Pb-Hf isotopic compositions, suggesting an origin of a thickened lower crust consisting mainly of garnet amphibolite. Although the Ridang subvolcanic rocks and Yardoi leucogranite show similar Sr-Nd-Hf isotopes to these adjacent coeval two-mica granites, perceptible differences in whole-rock major and trace elements can be observed. Broadly, these granites can be divided into high-Mg# granites (HMGs, the two-mica granites) and low-Mg# granites (LMGs, the Ridang subvolcanic rocks and Yardoi leucogranite). The former has relatively higher contents of total iron, MgO, Mg#, TiO2, P2O5, LREE, Y, Th, Sr, incompatible elements (Cr and Ni) and Eu/Eu* values, and lower contents of SiO2 and Rb/Sr and Rb/Ba ratios, thus is less evolved than the latter. According to recent studies of differentiation processes in silicic magma reservoirs, we proposed that the HMGs represent a congealed crystal mush that was composed of ‘cumulate crystals’ and a trapped interstitial liquid, while the LMGs represent the almost pure liquid that was extracted from the crystal mush. Modeling using the trace elements Sr and Ba shows that the extraction probably occurred when the crystallinity of the mush was ∼ 60%–63%, at least for the most evolved LMGs sample. The HMGs correspond to a residual crystal mush that had a terminal porosity of ∼ 21%–25% filled with a trapped interstitial liquid. Underplating of mafic magmas following slab breakoff of the Neo-Tethys oceanic lithosphere caused partial melting of the amphibolitic lower crust, which had been thickened to ~50 km prior to ~43 Ma.